Investigation of nozzle angle on the microstructure and abrasion resistance of jet electrodeposited Ni-TiC composites - Mengyu Cao; Dehao Tian; Chaoyu Li; BaoJin Wang; Xue Guo; Wei Li; Fengwu Zhang (Scientific Reports)
Abstract In order to study nozzle angle on the abrasion resistance of nickel-titanium carbide (Ni-TiC) composites, the jet electrodeposited Ni-TiC composite coating was fabricated at nozzle angles of 30°, 45° and 60°. The jet velocity and kinetic energy of the electrolyte at different nozzle angles within the given range of 30°–60° were simulated by means of COMSOL software. Additionally, the surface morphology, phase structure, and abrasion resistance of the Ni-TiC composites prepared at various jet angles were investigated using a scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction analysis, and a friction-abrasion testing machine, respectively. The simulation results indicated that at a nozzle angle of 45°, the jet speed and spraying pressure of the electrolyte were 3.17 m/s and 3.18 × 104 Pa, respectively. The Ni-TiC composites fabricated at nozzle angle of 45° had dense and smooth surface morphology with uniform distribution of TiC nanoparticles. Furthermore, at this nozzle angle, the composite demonstrated the smallest nanoparticle size (60.8 nm) and the highest TiC content (4.82 wt%). These findings confirm that the nozzle angle plays a crucial role in the distribution and incorporation of TiC nanoparticles, directly influencing the abrasion resistance of the composite. Notably, the Ni-TiC composite deposited at 45° exhibited the lowest friction coefficient and minimal mass loss, confirming its superior abrasion resistance.